Spatial mapping approach and irrigation water quality assessment for dryland management strategy in Abang district, Karangasem regency, Bali province - Luthfi Inayah; I Putu Gustave Suryantara Pariartha; Silvia Gabrina Tonyes (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
This study analyzes irrigation water quality and evaluates dryland suitability in Abang District, Karangasem Regency, Bali Province, using two assessment models: the National Sanitation Foundation Water Quality Index (NSF-WQI) and the Index of Surface Water Vulnerability to Pollution (IKAPP). Water samples from six irrigation points along Tukad Nyuling were analyzed for physical and chemical parameters, while rainfall, land use, and population density were integrated through spatial analysis. The results show that NSF-WQI values ranged between 69.96–79.78, indicating moderate to good irrigation quality, while the IKAPP average value of 23.69 represented a low vulnerability level. Spatial variation was influenced by topography, soil permeability, and land cover distribution. The integration of NSF-WQI and IKAPP provides a reliable framework for site-specific irrigation management, supporting sustainable dryland agriculture in tropical environments.